TABLE OF CONTENTS. I. TOBACCO ISSUES. (Tufts Archival Research Center, 2007)
Report containing assessments of many issues concerning tobacco manufacturers. Issues include cigarette taxes, environmental tobacco smoke (ETS) and fire safe cigarettes among many others. Includes a short background on the subject, an analysis of its effect, a plan for combating it, a fall back plan and an estimate of costs.